Advances in hearing aid technology. - Kerckhoff J; Listenberger J; Valente M (Contemporary Issues in Communication Science & Disorders)
Digital signal processing (DSP) has provided significant advances and improvements in hearing aid technology. These advances, and the increased processing speed that DSP offers, have resulted in improved and expanded features in current hearing aid technology. These advances have also served to expand the fitting range of amplification for patients who previously could not benefit from amplification. This article reviews the advances and supporting research in specific hearing aid features, devices, and assistive technology developments that allow a greater number of patients access to amplification. These features and devices include directional microphones, Bluetooth and other wireless technology, digital noise reduction, devices for patients with single-sided deafness, frequency transposition, selflearning and adaptation managers, and integrated real ear measures. Despite the changes in hearing aids created by DSP, limitations still exist. Additionally, peer-reviewed research is not yet available to support the reported benefits of some of these advances.